Continuous flow manufacturing quality in design and processes - Pierre, Guerindon C. (Manufacturing engineering and materials processing (Marcel Dekker, Inc.), 1995)
This work presents the fundamental principles of continuous flow manufacturing, furnishing a corporate strategy and set of operating rules that help create an environment where continuous flow manufacturing can flourish. A 10-step methodology for converting a traditional factory to a continuous flow operation is provided, and conventional manufacturing techniques are compared with the continuous flow approach.